LEARNING MODELS USING PROBING PROMPTING TECHNIQUES ASSISTED BY BLENDED LEARNING EDMODO TO IMPROVE MATHEMATICAL UNDERSTANDING ABILITY - Rahmawati Rahmawati; Jayanti Jayanti (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2019)
This study aims to see an increase in the ability of mathematical understanding of students using probing learning models prompting assisted by edmodo blended learning. In this model the researcher presents a series of questions that are digging and guiding so that a thinking process that links each student's knowledge and experience with new knowledge is occurring. learned. Research subject of 3rd Semester Student in Mathematics and Teacher Training Faculty, University of PGRI Palembang. This research method is Quasi-Experimental. The data of this study are of two types. Quantitative data was obtained through analysis of student answers on the KPM test which was carried out pretest and posttest, and qualitative data were obtained from observations of lecturer and student activities, and the results of interviews with students. Data analysis used: doing descriptive analysis of data and calculating normalized gain (normalized gain) pretest and posttest, Testing requirements analysis is the data normality test and variance homogeneity test of the whole quantitative data, and hypothesis testing in this study t test, t-test, Mann-Whitney U test, one-way ANAVA test or Kruskal-Wallis test. Hypothesis testing using SPSS-20 for Windows. The results of the data analysis concluded that 1) the increase in the ability of mathematical understanding of students who get learning by probing prompting assisted by edmodo blended learning is better than students who get conventional learning in terms of (a). all students (b) .KAM students